ChemInform Abstract: 9‐Alkylacridine Synthesis Using 2, 2‐Dimethoxypropane as Water Scavenger. Issue 3 (January 2015) - Bratulescu, George
Abstract The best results are obtained by using a (I)/(II)/Me2C(OMe)2/ZnCl2 = 1:1:2:2 ratio.